Anodic Oxidation of 3D Printed Ti6Al4V Scaffold Surfaces: In Vitro Studies - Talita Kathleen Correia de Sousa; Fátima Raquel Maia; Sandra Pina; Rui L. Reis; Joaquim Miguel Oliveira; João Pedro Aquiles Carobolante; Ana Lúcia do Amaral Escada; Guilherme Arthur Longhitano; Ana Paula Rosifini Alves (Applied Sciences, 2024)
This study focuses on the surface modification of Ti6Al4V scaffolds produced through additive manufacturing using the Powder-Bed Fusion Electron-Beam Melting (PBF-EB) technique. From our perspective, this technique has the potential to enhance implant osseointegration, involving the growth of a layer of titanium dioxide nanotubes (TiO2) on surfaces through anodic oxidation. Scaffolds with anodized surfaces were characterized, and the formation of a nanoporous and crystalline TiO2 layer was confirmed. The analysis of cell morphology revealed that cells adhered to the anodized surfaces through their filopodia, which led to proliferation during the initial hours. However, it was observed that the adhesion of Saos-2 cells was lower on anodized scaffolds compared to both built and chemically polished scaffolds throughout the cell culture period. The results obtained here suggest that while anodic oxidation is effective in achieving a nanoporous surface, cell adhesion and interaction were affected by the weak adhesion of cell filopodia to the surface. Thus, combining surface treatment techniques to create micro- and nanopores may be an effective alternative for achieving a favorable cellular response when the objective is to enhance the performance of porous titanium scaffolds in the short term.